Corn, Klansmen, and Coolidge: Structure and Framing in Social Movements. - McVeigh, Rory; Myers, Daniel J.; Sikkink, David (Social Forces (University of North Carolina Press), 2004)
This article examines how structural conditions and social movement frames interact to influence mobilization and political consequences of social movements. Mobilization efforts benefit when movement framing is congruent with local structural conditions. This mobilization, in turn, produces political leverage for the movement through its capacity to deliver support of its members and adherents. Its political advantage may be offset, however, if another of its key framing activities, the construction of collective identity boundaries, alienates the broader population and stimulates a backlash. Such backlash is also intimately connected to structural conditions because its potential is a function of the characteristics of the local population -- specifically, the proportion of the population alienated by the movement's boundary construction. We apply these arguments to the case of the Indiana Ku Klux Klan in the 1920s and show that while the Klan's diagnostic and prognostic framing may have resonated structurally and facilitated the Klan's mobilization efforts, its exclusionary boundaries frustrated its attempts to secure broader political gains. Reprinted by permission of the publisher.